The Role of Work Attachment in Mediating the Influence of Flexible Working Arrangement and Work-Life Balance on Job Satisfaction - Ni Komang Mirah Lestari; Made Surya Putra (Eduvest - Journal of Universal Studies, 2025)
A company must consider employee job satisfaction, as those who enjoy their work positively impact performance. PT Jasa Angkasa Semesta Tbk at I Gusti Ngurah Rai International Airport provides ground handling services but faces job satisfaction issues due to frequent overtime. This study analyzes the role of work engagement in mediating the effects of flexible working arrangements and work-life balance on job satisfaction among employees. Using a saturated sampling technique, the study surveyed all 117 employees through questionnaires and interviews, analyzing the data with descriptive and inferential statistics, specifically SEM-PLS. The findings reveal that flexible working arrangements and work-life balance both significantly improve job satisfaction and positively influence work engagement. Additionally, work engagement mediates the effects of both flexible working arrangements and work-life balance on job satisfaction. The research supports self-determination theory and offers practical solutions for enhancing job satisfaction within the company.